Principios básicos de los Cuidados Paliativos en Pediatría: Una revisión narrativa. - Fernando J. Menéndez Valdés; Enrique Méndez Veiga; Otto Valdes (Galicia Clínica, 2022)
Palliative care is a topic that is gaining more and more relevance. This therapy benefits the patient throughout their illness, for that reason, the scientific community is becoming aware of the importance of including such treatments in basic health services. Unfortunately, only some of the developed countries manage to have decent assistance in this type of care, and that is why governments and world organizations are taking more ambitious objectives in order to improve health quality even more. The evidence presented in this article shows the future possibilities of PC, focusing its attention on pediatric patients and their families, as well as the guidelines to be followed by the professional team to guarantee a complete and satisfactory approach.